Nietzsche's philosophy of religion - Young, Julian 1943- (Cambridge Cambridge University Press, 2006)
In his first book, The Birth of Tragedy, Nietzsche observes that Greek tragedy gathered people together as a community in the sight of their gods, and argues that modernity can be rescued from 'nihilism' only through the revival of such a festival. This is commonly thought to be a view which did not survive the termination of Nietzsche's early Wagnerianism, but Julian Young argues, on the basis of an examination of all of Nietzsche's published works, that his religious communitarianism in fact persists through all his writings. What follows, it is argued, is that the mature Nietzsche is neither an 'atheist', an 'individualist', nor an 'immoralist': he is a German philosopher belonging to a German tradition of conservative communitarianism - though to claim him as a proto-Nazi is radically mistaken. This important reassessment will be of interest to all Nietzsche scholars and to a wide range of readers in German philosophy.
1. Schopenhauer and 'man's need for metaphysics' -- 2. The birth of tragedy -- 3. Untimely meditations -- 4. Human, all-too-human -- 5. The gay science -- 6. Thus spoke Zarathustra -- 7. Beyond good and evil -- 8. On the genealogy of morals -- 9. The Wagner case -- 10. Twilight of the idols -- 11. The antichrist -- 12. Ecce homo -- 13. Epilogue : Nietzsche in history
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Nietzsche, Friedrich Wilhelm -- 1844-1900 -- Religion; Nietzsche -- Friedrich Wilhelm -- 1844-1900 -- Religion; Religion -- Philosophy -- History -- 19th century; Nietzsche, Friedrich Wilhelm ; 1844-1900 ; Religion; Religion ; Philosophy ; History ; 19th century; Nietzsche, Friedrich Wilhelm < 1844-1900>; Religion; Philosophie; Geschichte, 19. Jh